Success Factors for Using Case Management System in Italian Courts. Issue 1 (2nd January 2016) - Agrifoglio, Rocco; Metallo, Concetta; Lepore, Luigi
ABSTRACT: This study takes a first step toward understanding the effectiveness of e-court applications in Italy. The proposed research model to assess the success factors for using case management system was tested in two Italian courts. Analysis of survey data from 314 users, using structural equation modeling, reveals the explanatory role of the model and the salient contribution of system and information quality variables on court staff's performance. Our findings have important implications for theory and practice.